Development of System of Rice Intensification and Legowo planting systems on 'Rendengan' planting season using various rice varieties in different equatorial rainfall types in South Sulawesi. Issue 4 (July 2021) - Yassi, A; Mustari, K; Dariati, T
Abstract: This study is expected to address the water shortage in irrigated land with the use of adaptive varieties. The purpose of the study is to obtain a model of water management with System of Rice Intensification (SRI) method of planting systems combined with Legowo and the use of appropriate rice varieties for the equatorial rain-type region. The experiment was conducted in Sidrap Regency on sand textured soil, in the form of experimental research using Split Plot Design. The treatment of the water management of the wet-dry method, water saturated condition and intermittent as the main plot and varieties consist of Mekongga, Inpari-4 and Inpari-30 as a subplot. The results show that water management with the wet-dry method gives a better effect on plant height at 30 days after planting (DAP) (44.74 cm), 60 DAP (84.74 cm), the time of harvest (101.62 cm), panicle length (27.87 cm) and plots (per hectare) which was 223.75 kg (6.78 t), while the number of tillers 30 DAP (20.80 tillers), productive tillers (21.20 tillers) obtained in the discontinuous method. Development of varieties in paddy fields textured sand should use Inpari-4 in combination with water management in wet-dry method.